Bilateral microvascular second toe transfer for bilateral post-traumatic thumb amputation - Rajendra Nehete; Anita Nehete; Sandeep Singla; Harshad Adhav (Indian Journal of Plastic Surgery)
In bilateral thumb amputations, the functional impairment is serious and every attempt should be made to reconstruct the thumb. We report a case of bilateral post traumatic thumb amputation, reconstructed with bilateral second toe transfer. Only two such cases have been reported in literature so far. Though there are various modalities for the reconstruction of thumb, microvascular toe transfer has its own merits. The convalescent period is minimal with excellent function. It is bilaterally symmetric and aesthetically superior to the osteoplastic reconstruction. The technical details are discussed, and the long term functional and aesthetic results are presented.